(3PcQi LYaQ cGTa GdZWGAs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi Hf LYaQ cGTa GdZWGA, J (B1350 (3g`s
(3ChdgG (B:s
(3OeYI GdTHGH ; LGA aj GdYOO GdKGdK GdeUGOa GdKdGKGA (B20(3QLH (B358 (3GdehGab (B5 (3Cjdhd (B939 (3aj eLdI Gd(B.. (3dSfJgG GdChdi HGdYfhGf GdePchQ (B...s
(3BNQgG (B:s
.. (3hTgOJ GdCjOj hGdCQLd HeG cGfhG jaSOhf hLGA QHc hGdedc UaG UaG hLjA Hge jheFP jJPcQ GdEfSGf hCfi dg GdPcQi (B- (3hcGf GdNUeGf jdhP HYVgeG HHYV(B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\19s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs